The a to Z of Japanese Business - Picken, Stuart D.B. (Rowman & Littlefield Publishers, 2009)
Japanese industrial standards have long been the benchmark for quality products within Asia, indeed, within the world. Major Japanese industries like Toyota, Sony, and Honda, to name but a few, are household names that have contributed to this small island nation's status as the world's second largest economy. Japanese business practices and theories have permeated the mindset of its surrounding nations, and the country's long-term investment in the ever-growing Chinese market has further secured its status as an economic powerhouse. The A to Z of Japanese Business is an examination of the origins and characteristics of Japan's business culture. This handy reference book includes most of the important words or company names that foreign business people visiting Japan might encounter and provides an overview of Japanese corporate culture both from an historical standpoint and with reference to its most distinctive features as they affect organization and management. This is accomplished through its historical chronology detailing significant events of the past as well as recent developments within the Japanese economy and business world in general, various appendixes offering lists of business expressions that are in daily use along with a selection of the most commonly used business proverbs, a bibliography, and hundreds of cross-referenced dictionary entries on Japanese companies, their founders and managers, the ever-present bureaucratic bodies, and progress in the major industries.